Beneficial effects of renal denervation on cardiac angiogenesis in rats with prolonged pressure overload. (12th October 2016) - Lu, D.; Wang, K.; Wang, S.; Zhang, B.; Liu, Q.; Zhang, Q.; Geng, J.; Shan, Q.
Abstract: Aim: Renal denervation (RDN) has beneficial effects on cardiac remodelling and function in resistant hypertension. We aimed to investigate the impact of RDN on cardiac angiogenesis during prolonged pressure overload. Methods: Cardiac pressure overload was reproduced by transverse aorta constriction (TAC) procedure in adult Sprague Dawley male rats ( n = 35). RDN/sham‐RDN procedure was performed in surviving rats at 5 weeks after TAC. Results: Five weeks post‐TAC, transthoracic echocardiography revealed that myocardial hypertrophy occurred in TAC rats, with ejection fraction and fractional shortening not significantly changed. At the end of 10 weeks, cardiac systolic function was preserved in RDN group, but not in sham group. CD31 immunohistochemical staining showed that RDN‐treated rats had higher cardiac capillary density than sham rats. However, no significant between‐group difference was observed in the kidneys. A decreased protein expression of left ventricle vascular endothelial growth factor (VEGF) was observed in sham group, while RDN attenuated this decrease. Compared with sham, RDN resulted in a higher protein expression of VEGF receptor 2 (VEGFR2) and phosphorylated endothelial nitric oxide synthase (p‐eNOS) in the heart. Conclusion: Renal denervation benefits cardiac angiogenesis during sustained pressure overload, involving regulation of VEGF and VEGFR2 expression as well as activation of eNOS.